Contaminated Dextrose Normal Saline: A Cause of Endogenous Endophthalmitis in an Immunocompetent Subject - Mridu Chaudhry; Shikha Baisakhiya; MS Bhatia; Ritesh Gupta; Aakarsh Bajaj (Delhi Journal of Ophthalmology)
Endogenous endophthalmitis is an intraocular infection caused by haematogenous spread of microorganisms from distant foci. It accounts for 2-8% of all cases of endophthalmitis. The common causative organisms include Staphylococcus aureus, Streptococcus pneumoniae, Pseudomonas and Klebsiella. Candida and Aspergillus are the common fungal isolates reported. Endogenous endophthalmitis usually occurs in immunocompromised subjects but increasingly a large number of cases have been reported among immunocompetent patients. We report a case of endogenous endophthalmitis in an immunocompetent subject after intravenous fluid therapy for gastroenteritis.